ANALISIS PELAKSANAAN FUNGSI LEGISLASI DEWAN PERWAKILAN RAKYAT DAERAH KABUPATEN HUMBANG HASUNDUTAN TAHUN 2025 - Trido Pasuna Purba; Ishak ' (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2026)
ABSTRACT The legislative function is a fundamental function of the DPRD in the local government system which includes planning, discussion, and approval of Regional Regulations (Perda). The non-optimal implementation of this function is reflected in the absence of a Draft Regional Regulation (Ranperda) initiative of the DPRD in the 2025 Regional Regulation Formation Program (Propemperda) and the failure to achieve the maximum legislative target is the urgency of this study. This condition is even more relevant considering that 2025 is the first year of the term of office of the Humbang Hasundutan Regency DPRD for the 2024-2029 period which is dominated by new members. This study uses a descriptive qualitative approach based on the theory of legislation and the theory of political representation by Hanna Fenichel Pitkin. Data collection was carried out through in-depth interviews and documentation studies on Propemperda, meeting minutes, and regional legal products. Analysis using Miles and Huberman's interactive models includes data reduction, data presentation, verification, and conclusion drawn. The results of the study show that the implementation of the legislative function of the Humbang Hasundutan Regency DPRD in 2025 has been running procedurally, but it has not been optimal substantially. At the planning stage, the Propemperda is dominated by proposals from regional heads without a single Ranperda initiative of the DPRD. At the discussion stage, a number of Ranperda were delayed due to weak sociological foundations, clashes with socio-cultural values of the community, and limited budget support. This study concludes that strengthening the legislative function of the DPRD needs to be directed at three aspects of belief, optimizing the use of the right of initiative, increasing institutional capacity, and strengthening the representation of community aspirations in the process of forming regional regulations. Keywords: Legislative Function, DPRD, Political Representatives, Propemperda